Protection is better than management to maintain tree species: A case study of lesser-Himalayan moist-temperate forests of Pakistan - Waseem Hayat (Elsevier, 2021)
Forests constitute about thirty percent of total land of district Abbottabad in Khyber Pakhtunkhwa province, Pakistan. However, local populations utilize these forests to fulfill the requirements of fodder, fuelwood and sawn timber. Most studies; based on exploration of the composition of vascular and non-vascular floral species after human-induced deforestation have been conducted in protected areas of Abbottabad. Present study was focused on forests’ inventory in unprotected area to assess the implications of forest management practices through quadrate-plot survey method with systematic sampling design. The abundance, frequency, dominance, density and population of tree species as well as Importance Value and Family Value Indices were higher in reserved forests. However, Shannon-Weiner Index, Species Richness, Evenness and Simpson Indices were higher in community forests indicating the higher deterioration of community forests. Statistical analysis supported the significance of acquired results. The findings support the existence of intact tree vegetation in reserved forests can be due to less utilization of reserved forests by local populations. Forests’ protection has positively influenced the structure and density of tree vegetation stand in reserved forests. The study would offer information for wise management of forests in study area as well as other non-protected areas of district. The study supports an active forests management at local levels to contribute in global forests’ conservation.